Etika Penggunaan Kecerdasan Buatan dalam Pendidikan Hukum - Yanto, Oliviani (UI Scholars Hub, 2025)
This article aims to formulate the ethics of using Artificial Intelligence (AI) in legal education. Legal education held by the Faculty of Law is a center for the development of excellence in legal science in order to generate competent graduates. The ability to provide a legal opinion on a legal issue is a competency that every law graduate must have. In this era, law students can easily command AI to construct legal opinion without going through the legal research process. The implication for Faculty of Law is that they fail to prepare law graduates who are able to produce legal opinion. The issue to be discussed in this article is how is the role of Faculty of Law in dealing with the developmet of AI in the midst of educating future law graduates. This article argues that ethics occupies an essential aspect that should be a concern for Faculty of Law because with the systematized ethics, law students can act with caution in utilizing AI. The application of ethics also applies to legal academics in Faculty of Law as those who educate law students. There are 3 (three) ethics proposed by the Author, namely reviewing, honesty, and carefulness. The formulation of these ethics is carried out by examining the existing regulation related to AI in Indonesia and then comparing it with the regulation related to AI in Europe. This research is conducted using normative legal research methods through statutory approach and comparative approach.